2016
DOI: 10.1080/10773525.2016.1243081
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with work-related eye injuries in Bosnia and Herzegovina

Abstract: Promotion of eye safety is needed countrywide. Occupational eye protection is a priority due to the relatively proportion of eye injuries and the workplace being a relatively controlled environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
2
18
1
2
Order By: Relevance
“…16 The highest percentage observed in other studies was in the 25-34 age group in Western Turkey 15 and the 16-24 age group in Modena (Italy). 5 However, we observed more incidence of WREI for 100 000 insured in the lowest age group (16)(17)(18)(19)(20)(21)(22)(23)(24) in our study, and this incidence decreases with age. We only analysed workers population, and we think this is why we found more eye injuries in the lowest age group.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…16 The highest percentage observed in other studies was in the 25-34 age group in Western Turkey 15 and the 16-24 age group in Modena (Italy). 5 However, we observed more incidence of WREI for 100 000 insured in the lowest age group (16)(17)(18)(19)(20)(21)(22)(23)(24) in our study, and this incidence decreases with age. We only analysed workers population, and we think this is why we found more eye injuries in the lowest age group.…”
Section: Discussioncontrasting
confidence: 54%
“…As in other studies, 5 we observed the highest incidence and percentage of WREI in industry workers. Agriculture was the most affected group in other studies 19 20 but in all of them, services was the least affected group. This is due to the lower risk of trauma or other external agents that can affect services workers.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies indicated occupational related eye injury was the major cause with differences in work types between countries. [18][19][20] This study highlighted that a high number of eye injury occurred in 40 to 60 years old age group during work that involved an electric grass trimmer. This may in part reflect the low rate of using eye-protective equipment when undertaking high-risk work.…”
Section: Discussionmentioning
confidence: 84%
“…En el 2007, la OMS reportó que los países de medianos o bajos ingresos tenían elevadas tasas de lesiones oculares institucionales, especialmente en industrias caseras y no reguladas [10] . En el 2016, un estudio realizado en Bosnia y Herzegovina reportó que los trabajadores agrícolas, de empresas caseras o informales, tenían ocho veces más probabilidades de sufrir lesiones oculares relacionadas con el trabajo en comparación con los trabajadores de empresas formales [11] .…”
Section: Introductionunclassified